Seasonal analysis of Southern Ocean copepod ecology using a moored sediment trap - Atherden, Florence; Ward, Peter; Blackbird, Sabena; Wolff, George; Tarling, Geraint A.; Manno, Clara (Frontiers in Marine Science, 2025)
The Southern Ocean is a globally significant site of carbon sequestration with the copepod community exerting a strong influence on the carbon flux. Currently, a holistic understanding of Southern Ocean copepod ecology is limited by a lack of data, particularly during winter. This study analyzed the composition and abundance of copepods caught in a sediment trap (400 m depth) in the Northeast Scotia Sea, providing a view of year-round copepod community dynamics. We found strong seasonal trends in abundance and composition of copepod taxa, with Calanus simillimus and Metridia spp dominating throughout. The capture of Metridinidae copepods likely occurred as they carried out their pronounced diel vertical migrations (DVM). The disproportionate abundance of male specimens of Metridia spp., as well as another member of the Metridinidae, Pleuromamma robusta, indicates sex-specific differences in their DVM ranges, with males remaining deeper. The C5 developmental stage of C. simillimus showed a distinct seasonal pattern, characterized by high abundances in autumn followed by low numbers in winter. We propose that this reflects an autumnal seasonal descent beyond which their fate could be one of three scenarios. Firstly, that these individuals seasonally migrate deeper than the sediment trap depth but remain active and feed on deep particulate matter. Secondly, that they become dormant whilst at this depth and respire their fat reserves. Thirdly, that they become dormant but at shallower depths, at and around the depth of the sediment trap, where they remain static and are not captured. Each of these scenarios has different implications for the seasonal carbon flux generated by C. simillimus. This study highlights the importance of understanding species-specific copepod ecology and emphasizes the need to collect ecological data over full annual cycles.